A STING-based biosensor affords broad cyclic dinucleotide detection within single living eukaryotic cells - Alex J. Pollock (Nature Portfolio, 2020)
Cyclic dinucleotides are conserved second messengers but current detection methods are limited. Here the authors engineer a Förster resonance energy transfer (FRET) based biosensor, BioSTING, which gives real-time in vitro detection of these nucleotides.